Analysis of the animal feed to poultry value chain in Zambia - Paul C. Samboko; Olipa Zulu-Mbata; Antony Chapoto (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Rapid population growth, urbanization, and income growth are triggering increased demand for high-value agricultural products across Southern Africa with scope for gains from trade and regional integration. We analyse the animal feed to poultry value chain in Zambia focusing on the industry capabilities with a view to enhancing its competitiveness and production for the regional market. The industry has exhibited rapid growth with investments, which has increased competition to consumers' benefit. However, challenges remain if it is to contribute to the regional market; animal feed input production and productivity remain low despite improvements. Similarly, produced poultry is in low quantities. Consequently, there is limited export of products due to higher prices. Enhancing value chain capabilities will require technology investments and public expenditure allocations that enhance productivity and production of animal feed inputs, and limited government intervention in maize marketing and trade which adversely impacts on maize prices.
Keywords: L66; O55; Q13; O25; 330; value chain; Southern Africa; poultry; animal feed; Zambia